PROSPECTS FOR IMPROVING PRODUCT QUALITY IN TEXTILE INDUSTRY ENTERPRISES BASED ON QUALITY POLICY SYSTEMS: PROSPECTS FOR IMPROVING PRODUCT QUALITY IN TEXTILE INDUSTRY ENTERPRISES BASED ON QUALITY POLICY SYSTEMS - Qakhramonov, Mukhammadali; Khosimov , Akhtamhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The enterprises of the textile industry are not only the most important of the existing enterprises in Uzbekistan, but also help to develop this industry. therefore, the unsatisfactoriness of harmonization with the requirements of national and international standards in textile enterprises and the current unsatisfactory quality management systems in textile enterprises, as well as the import of products made in Uzbekistan to foreign markets, increasing the export potential and the quality and safety of products is an obstacle to increasing trust. Unveiling this potential, forming a textile network in our country that meets the requirements of the times is one of the priority directions of the development of the national economy. Therefore, it is obvious that it is necessary to introduce a quality management system recognized at the international level and meeting global requirements in the enterprises of the textile industry in Uzbekistan. In this article, we recommend establishing a quality policy based on the requirements of the quality management system (SMT, ISO 9000 standard) for textile industry enterprises and introducing modern quality system requirements. That is, it became clear that there are many problems and gaps in the implementation of the unique (SMT) quality management system of textile industry enterprises. Modern quality management system and electronic quality management system (EQMS) and PDCA cycle were developed for textile industry enterprises. As a first step, the scientific work carried out on quality policy was reviewed and the changes after the introduction of the quality management system to textile enterprises were thoroughly analyzed.